2017
DOI: 10.17925/enr.2017.12.01.31
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation in Multiple Sclerosis – Resilience in Practice

Abstract: In recent years, enormous strides have been made in increasing the range and efficacy of disease-modifying drugs available for the treatment of multiple sclerosis (MS) in its early and remitting stages, and more continue to emerge. Another equally important concept of successful treatment of MS is neurorehabilitation, which must be pursued alongside these medications. Key factors that contribute to the impact of neurorehabilitation include resilience and neuroplasticity. In the former, components such as nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This goal could be achieved through a multidisciplinary strategy where the clinical team participated in the patient’s needs and therapists’ assessment of problems (mobility, self-care ADL, communication, daily occupations, and social interactions). Several studies demonstrated that this kind of inpatient or outpatient rehabilitation programs may reduce disability and bladder dysfunction, and improve participation in neurological patients [ 59 ].…”
Section: The Metaverse Could Enhance the Translation To The Holistic ...mentioning
confidence: 99%
“…This goal could be achieved through a multidisciplinary strategy where the clinical team participated in the patient’s needs and therapists’ assessment of problems (mobility, self-care ADL, communication, daily occupations, and social interactions). Several studies demonstrated that this kind of inpatient or outpatient rehabilitation programs may reduce disability and bladder dysfunction, and improve participation in neurological patients [ 59 ].…”
Section: The Metaverse Could Enhance the Translation To The Holistic ...mentioning
confidence: 99%
“…Furthermore, research shows that the newly formed network connections in the brains of MS patients have a higher complexity level than the previous architecture of the healthy brain, unlike other conditions, such as stroke, where brain tissue restoration follows its original network patterns [ 47 , 48 , 49 , 50 , 51 , 52 ]. In addition, the neuroplasticity of patients with MS could decline after two years of an initial increase, thus leading to a progression of the disease and disability [ 53 , 54 ].…”
Section: The Effect Of Neurorehabilitation On the Neurobiological Par...mentioning
confidence: 99%